PENGARUH CAPITAL ADEQUACY RATIO (CAR), BOPO DAN NON PERFORMING LOAN (NPL) TERHADAP KINERJA KEUANGAN PERBANKAN DI INDONESIA - Matindas, Anggria Maya; Pangemanan, Sifrid S.; Saerang, David P.E. (JURNAL RISET AKUNTANSI GOING CONCERN, 2015)
This study aimed to determine the effect of the Capital Adequacy Ratio (CAR), ROA and Non-Performing Loans (NPLs) of the return on assets (ROA) banking companies listed in Indonesia Stock Exchange 2008-2010 period. Data obtained from the Financial Report issued by Bank Indonesia with the time period of 2008 to 2010. The population of this study were 28 companies and a total sample of 22 companies with a purposive sample passing phase. Analysis techniques will be used in this research is regression to obtain a comprehensive picture of the relationship between one variable with another variable. The results showed that the variable Capital Adequacy Ratio (CAR) is not significant and has a negative relationship to the ability of return of assets (ROA), ROA indicates that the variable ROA ROA significant effect on the banking company. While the Non Performing Loan (NPL) had no significant effect on ROA banking company. The result is expected that the variable Capital Adequacy Ratio (CAR), ROA, and Non-Performing Loans (NPLs) could be considered by the bank management in managing the company to improve the performance of the company.